Promoting Effect of L-tyrosine Supplement on New Zealand Rabbit Bucks' Performance and Reproduction Through Upregulation of Steroidogenic Markers - Mahmoud, Shawky; Saad, Michel; El-Shehawi, Ahmed M.; Farrag, Foad; Abo Ghanima, Mahmoud M.; Dawood, Mahmoud A. O.; Shukry, Mustafa (Frontiers in Veterinary Science, 2020)
Delayed puberty and reduced fertility during summer months considered one of the most problems encountered in rabbit production. Therefore, this study aimed to improve the performance of male New Zealand rabbits using L. tyrosine. For this purpose, 30 male New Zealand rabbits of two months' age are used. They were randomly assigned into two groups: a control and L. tyrosine treated one (100 mg/kg body weight). After one month, three bucks from each group were slaughtered, and half of the treated group was administered a further similar oral dose of L. tyrosine while the second half was left without further treatment. Weekly blood samples collected from all groups for hormone assay of testosterone, T3, and T4. The results revealed that total body weight and serum testosterone, T3, and T4 significantly increased with advancing age in all groups. L. tyrosine induced a further dose-dependent, significant increase in body weight, GSI and serum testosterone, T3, and T4 as compared to control. Testes descent in the scrotum at the end of the 3rd month age of the control group and two weeks earlier in L. tyrosine treated one. Semen collection was firstly performed in the middle of the 4th month age of L. tyrosine treated group and one month later in control one. L. tyrosine induced a significant increase in semen volume, sperm count, mass and individual motility, and a live sperm percentage, but abnormalities were significantly decreased (P < 0.01). As well as L. tyrosine treated group showed upregulation mRNA expression of steroidogenesis markers STAR, CYP11A1 and 3B-HSD in testicular tissue Histological sections in testes, at the end of the 3rd month age, showed free spermatozoa in the lumen of seminiferous tubules in the treated group. Still, it reaches to the spermatocyte stage only in control one. The study recommends the addition of L. tyrosine in a dose of 100 mg/kg b. wt. to induce puberty and to improve the fertility of male New Zealand rabbits during summer months.